2014
DOI: 10.1007/s00406-013-0483-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain activation during response inhibition and error processing in subjects with Internet gaming disorder: a functional magnetic imaging study

Abstract: The aim of the present study was to evaluate the impulsivity and brain correlates of response inhibition and error processing among subjects with Internet gaming disorder (IGD). We evaluated the response inhibition and error processing by functional magnetic resonance imaging (fMRI) in subjects with IGD and controls. Twenty-six men with IGD for at least 2 years and 23 controls with no history of IGD were recruited as the IGD and control groups, respectively. All subjects performed the event-related designed Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(73 citation statements)
references
References 51 publications
5
63
3
2
Order By: Relevance
“…Comparisons with pathologic gamblers indicate that low conscientiousness and low extraversion are specific characteristics of IGD [26]. High levels of impulsivity also have been associated with IGD [27,28]. Lastly, a prospective study found that high impulsivity is a risk factor for IGD [19].…”
Section: Factors Associated With Internet Gaming Disorder (Igd)mentioning
confidence: 95%
See 1 more Smart Citation
“…Comparisons with pathologic gamblers indicate that low conscientiousness and low extraversion are specific characteristics of IGD [26]. High levels of impulsivity also have been associated with IGD [27,28]. Lastly, a prospective study found that high impulsivity is a risk factor for IGD [19].…”
Section: Factors Associated With Internet Gaming Disorder (Igd)mentioning
confidence: 95%
“…This finding suggests that the IGD group had impaired response inhibition under gaming distraction; that is, activations of the right DLPFC and superior parietal lobe were insufficient for maintaining the cognitive control and attention allocation required for response inhibition under gaming cue distraction. Ko et al [28] further investigated brain activation of response inhibition in a study of the go/ nogo task in an event-related study of subjects with IGD. Compared with controls without IGD, the IGD group exhibited higher brain activation when processing response inhibition over the left orbital frontal lobe and bilateral caudate nucleus.…”
Section: Response Inhibition In Igdmentioning
confidence: 99%
“…Some researchers (Cao et al, 2007;Shapira, Goldsmith, Keck, Khosla, & McElroy, 2000;Young, 1998) have suggested that internet addiction, including IGD, was an impulse disorder or was at least related to impulse control. Recent studies (Cao et al, 2007;Chen et al, 2015;Ko et al, 2014Ko et al, , 2015Luijten, Meerkerk, Franken, van de Wetering, & Schoenmakers, 2015) have found that adolescents with IGD/internet addiction had greater impulsivity compared to that of healthy controls (HCs). Behavioral studies using impulse control-related tasks (e.g., Go-NoGo, Go-Stop, and/or Stroop paradigms) have demonstrated behavioral control difficulties in IGD adolescents (Cao et al, 2007;Dong, Zhou, & Zhao, 2010Lin et al, 2012;Liu et al, 2014;Luijten et al, 2015).…”
mentioning
confidence: 99%
“…Accumulating neuroimaging studies have indicated the neural substrates of the greater impulsivity of IGD adolescents. Recently, functional neuroimaging studies revealed that IGD adolescents exhibit aberrant activations in the fronto-striatal network, the supplemental motor area, the cingulate cortex, the insula, and the parietal lobes during the performance of impulse control-related tasks compared with HCs Ding et al, 2014;Ko et al, 2014;Liu et al, 2014;Luijten et al, 2015). Moreover, aberrant effective connectivity in the response inhibition network and altered resting-state functional connectivity between multiple brain regions (Kim et al, 2015;Ko et al, 2015) have also been revealed to be correlated with impulsivity in IGD adolescents.…”
mentioning
confidence: 99%
“…The authors furthermore found an association of the G/G genotype of HTR1A (rs6295) with poor working memory in the premenstrual phase which points to a reduced serotonin neurotransmission in PMDD. The Go/ Nogo task was also used by Ko et al [3] in their fMRI study of Internet gaming disorder (IGD) focusing on impulsivity and brain correlates of response inhibition and error processing in 26 affected subjects compared with 23 controls. The authors found not only the expected higher impulsivity in IGD patients but also higher brain activation on response inhibition, especially over the left frontal lobe and bilateral caudate nucleus, while the activation over the right insula was lower compared with controls.…”
mentioning
confidence: 99%